Pembuatan Pulp Dari Rumput Gajah Dengan Pelarut Organik Asam Formiat - Syahputra, Dede; Helwani, Zuchra; Rionaldo, Hari; Zulfansyah, Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Elephant grass is lignocellulosic material that has the potential as raw material in pulping process. The objective of this research is to study effect of operational condition on the characteristic of pulp. Effect of the process condition were studied by Response Surface Methodology (RSM) with Central Composite Design (CCD). Pulping Experiment were carried out at the boiling temperature of cooking liquorat atmosphere ic pressure with 40 gram of elephent grass with a concentration of formic acid were 60%, 70%, and 80%, cooking time were 60 minutes, 120 minutes, and 180 minutes, solid to liquor ratio were 10/1, 15/1, and 20/1, and catalyst HCl was 0,1%. The result showed that pulp of the elephant grass have yield pulp of 53,6% - 73,7%, lignin content of 11% - 19,5%, and tensile index of 47,93 – 205,491 Nm/g. Keywords: organosolv pulping, formic acid, elephant grass, CCD, RSM.